(untitled) (European Journal of Education and Psychology, 2010)
The aim of this study was to obtain a culturally adapted Spanish version of the “Revised family communication patterns instrument (RFCP), using rigorous procedures in the retro-translation process and in the subsequent empirical study. The sampling consisted of 455 university students and two subscales for the conversation orientation were obtained (“Ideas expression” and “Differences acceptance”) and two for the conformity orientations (“Differences rejection” and “Obedience encourage”). All the scales proved to have good psychometric qualities and suitable convergent, concurrent and content validity, yet it is necessary to go more deeply into the conformity orientation. The construct validity was supported by a confirmatory factorial analysis showing that the RFCP is a useful instrument for family assessment.